Nonlinear Control Applied in Jump Attenuation of a Non-ideal System - Tusset, A. M.; Kossoski, A. [UNESP]; Bueno, A. M. [UNESP]; Balthazar, Jose Manoel [UNESP]; Felix, J. L.P.; Cunha, A.; Avanço, R. H. (Springer Nature, 2022)
This work proposes the attenuation of the Sommerfeld effect (jump phenomenon) present in a non-ideal oscillator thought the use of different nonlinear controllers. The non-ideal system is composed of a beam-like mechanical structure excited by a limited power supply, in this case an unbalanced direct current motor. Two different control techniques are considered. The first controller has its feedback gain obtained through the SDRE (State-Dependent Riccati Equation) technique in conjunction with a feedforward gain. The second controller is based in the SMC (Sliding Mode Control) technique. Numerical simulations show that the two proposed control strategies are effective in suppressing the jump phenomenon, and thus keeping the structure vibration of the studied system at desirable levels.
Keywords: Non-ideal system; SDRE control; Sliding Mode Control; Sommerfeld effect